REPRESENTASI EMOSI DAN MAKNA RELIGIUS DALAM TUTURAN ENZY STORIA PADA PODCAST “DANIEL TETANGGA KAMU”: KAJIAN PSIKOLINGUISTIK - Tachi, Lely Nur; Suroso, Eko (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
This research aims to analyze the representation of emotions and religious meanings in Enzy Storia's speech on the Daniel Neighbor Kamu podcast episode "Through Tahajud Prayer, Enzy Storia Receives God's Miracles?". This study is based on a psycholinguistic approach that focuses on the relationship between the speaker's psychological processes and linguistic forms in oral communication. The research data was in the form of a transcript of a conversation between Enzy Storia and Daniel Mananta which was analyzed qualitatively descriptively with the technique of interpreting the meaning and context of speech. The results of the study showed that Enzy's linguistic expression reflected multi-layered emotional dynamics, starting from confusion, sadness, to the achievement of spiritual calm. Diction choices such as "I'm sincere" and "Oh Allah, if this is my way" show a change in self-perception from the crisis phase to religious acceptance. Through language, Enzy emphasizes the shift in emotional orientation from suffering to sincerity, as well as showing the function of language as a medium of psychological healing. This research proves that religious language is not only a means of expression of faith, but also a therapeutic instrument that helps individuals reorganize emotional and spiritual balance. Thus, Enzy's speech becomes an authentic representation of the relationship between language, emotions, and faith that reinforce each other in modern human communication. ABSTRAK Penelitian ini bertujuan menganalisis representasi emosi dan makna religius dalam tuturan Enzy Storia pada podcast Daniel Tetangga Kamu episode “Lewat Doa Tahajud, Enzy Storia Terima Mujizat Tuhan?”. Kajian ini berlandaskan pendekatan psikolinguistik yang menitikberatkan pada hubungan antara proses psikologis penutur dan bentuk linguistik dalam komunikasi lisan. Data penelitian berupa transkrip percakapan antara Enzy Storia dan Daniel Mananta yang dianalisis secara kualitatif-deskriptif dengan teknik interpretasi makna dan konteks tuturan. Hasil penelitian menunjukkan bahwa ekspresi linguistik Enzy mencerminkan dinamika emosi yang berlapis, dimulai dari kebingungan, kesedihan, hingga pencapaian ketenangan spiritual. Pilihan diksi seperti “aku ikhlasin aja” dan “Ya Allah, kalau memang ini jalan aku” menunjukkan perubahan persepsi diri dari fase krisis menuju penerimaan religius. Melalui bahasa, Enzy menegaskan pergeseran orientasi emosional dari penderitaan menjadi keikhlasan, serta memperlihatkan fungsi bahasa sebagai media penyembuhan psikologis. Penelitian ini membuktikan bahwa bahasa religius tidak hanya sarana ekspresi keimanan, tetapi juga instrumen terapeutik yang membantu individu menata kembali keseimbangan emosional dan spiritual. Dengan demikian, tuturan Enzy menjadi representasi autentik hubungan antara bahasa, emosi, dan iman yang saling memperkuat dalam komunikasi manusia modern.